DOES FINANCIAL DISTRESS LEAD TO CORPORATE FRAUD? - Christian, Natalis; Mardianto (Global Financial Accounting Journal, 2025)
Purpose – This study investigates the effect of financial distress on corporate fraud by utilizing various financial distress indicators to assess their influence on fraudulent corporate behaviour. Research Method – The study employs panel data regression analysis using data from 210 companies listed on the Indonesia Stock Exchange (IDX) over the 2015–2019 period. Financial distress is measured using three indicators: Z-Score, Zmijewski Score, and Grover Score. Findings – Descriptive statistics show that, on average, companies on the IDX are not generally experiencing financial distress nor engaging in corporate fraud. However, hypothesis testing provides empirical evidence that financial distress significantly affects corporate fraud. Among the indicators, the Grover Score exhibits the strongest influence on the likelihood of fraud occurrence. Implication – The findings offer theoretical insights for academics and practical implications for regulators and corporate governance professionals. The study suggests that revisiting the conceptual framework and re-grouping indicators in measuring financial distress can contribute to the development of future theories and preventive measures related to corporate fraud.